(untitled) (Boca Raton, FL, 2002)
As trends in foodborne disease continue to rise, the effective identification and control of pathogens becomes ever more important for the food industry. With its distinguished international team of contributors, Foodborne Pathogens provides an authoritative and practical guide to effective control measures and how they can be applied to individual pathogens.
An toàn và quản lý chất lượng nông sản,Quản lý chất lượng và luật thực phẩm
Keywords: Foodborne diseases,Bệnh do thực phẩm